Processing math: 0%

Wednesday, November 25, 2015

Some Results in Geometric Algebra

\newcommand{\abs}[1] {\left\vert #1 \right\vert}

Cramer's Rule

The roots of Cramer's rule have always seemed a little mysterious. If we have a system of equations

a_1 x_1  + b_1 x_2 = c_1
a_2 x_1 + b_2 x_2 = c_2

Then Cramer says
x_1 = \frac{\det  \begin{bmatrix} c_1 & b_1 \\  c_2 & b_2  \end{bmatrix}}{\det  \begin{bmatrix} a_1 & b_1 \\  a_2 & b_2  \end{bmatrix}}

and

x_2 = \frac{\det  \begin{bmatrix} a_1 & c_1 \\  a_2 & c_2  \end{bmatrix}}{\det  \begin{bmatrix} a_1 & b_1 \\  a_2 & b_2  \end{bmatrix}}

That determinants play any role in isolating linear parameters is not obvious. So it's delightful how geometric algebra shines light on this.

A note on notation: in this section, latin letters are vectors and greek letters are scalars, so that

x = \alpha a + \beta b

is a vector equation relating vector x to vectors a and b. The gift we are given by geometric algebra is that vectors become invertible, so we can write, since a \wedge a = 0 :

a \wedge x = \beta a \wedge b
\beta = \frac {a \wedge x}{a \wedge b}

And similarly,

\alpha = \frac {x \wedge b}{a \wedge b}

so that

x = \left( \frac {x \wedge b}{a \wedge b} \right) a +  \left( \frac {a \wedge x}{a \wedge b} \right) b

Now, in \mathbb{R_2}, 2-vectors are pseudoscalars, and pseudoscalars are scalar multiples of I, the unique (up to a scalar) highest-grade multivector. The determinant is just that scalar (say, \lambda): a \wedge b = \lambda I. So we can write:

x = \left(\frac {\det (x \wedge b) I}{\det (a \wedge b)  I} \right) a +   \left( \frac {\det (a \wedge x) I}{\det (a \wedge b) I} \right) b


x = \frac {\det (x \wedge b) }{\det (a \wedge b)  } a +   \frac {\det (a \wedge x) }{\det (a \wedge b) }  b

That's the fastest path to Cramer's Rule anywhere.

BAC-CAB

Consider the product of a vector and bivector: a (b \wedge c).

\frac{1}{2} a (bc - cb)

\frac{1}{2} (abc - acb)

Since ab =2 a \cdot b -ba, we can write

\frac{1}{2} (2 a \cdot b \; c - bac -2a \cdot c \; b -cab )

\begin{equation} \label{eq1} a \cdot b c - a \cdot c b -\frac{1}{2} (bac-cab) \end{equation}

The last two terms can be expanded as before:

- \frac12(bac-cab) = -b a \cdot c + \frac{bca}{2}  + c a \cdot b - \frac{cba}{2} 

So in the expanded \eqref{eq1}, the dot products combine to give us

2  a \cdot b  c - 2  a \cdot c  b  + \frac{(bc-cb) a}{2}

So finally

a (b \wedge c)  = 2  ( a \cdot b  c -  a \cdot c b ) + (b \wedge c) a

\frac{ a (b \wedge c) - (b \wedge c) a}{2} =  a \cdot b c - a \cdot c b

a \cdot (b \wedge c) = a \cdot b c - a \cdot c b

This is a handy result.  And, not restricted to \mathbb{R^3}.

Using the Dual to Exchange Dot and Wedge Products

We will develop a nice result with the dual operation that lets us exchange dot and wedge products.

For any multivector A, we can write A = A^\perp I, where A^\bot is whatever multivector you need to multiply with I to get A, called the dual of A. In other words, taking the dual is multiplying on right with I^{-1}. Now consider the dual of AB

(AB)^\bot = AB^\bot

This can be confirmed by examining (AB)I^{-1} = ABI^{-1}.

Now compare grades of this expression, and conclude that the largest grades give us

(A \cdot B)^{\bot} = A \wedge B^\bot

and the smallest grades give us

(A \wedge B)^{\bot} = A \cdot B^\bot

Gibbs' Vector Product

The dual lets us move between Gibbs-style cross products a \times b and geometric products:
  a \times b \equiv (a \wedge b)^{\bot}

Of course Gibbs' cross product is only defined in \mathbb{R^3}.

Here's an example, which for some readers may complete the BAC-CAB story:
\begin{align} a \times (b \times c) & = \{ a \wedge  (b \times c) \} ^\bot \\ & = a \cdot (b \times c)^\bot \\ & = -a \cdot b \wedge c \end{align}
 
Another:
\begin{align} a \cdot b \times c & = a \cdot (b\wedge c)^\bot \\ & = (a \wedge b \wedge c)^\bot \end{align}

Rotations

On our way to describing angular momentum under a geometric algebra framework, we need to establish a preliminary object known as a rotor. And on the way to the rotor, we need to work through reflections. Consider a reflection axis n (n is a unit vector) and a vector v.

v = v n n^{-1}
= [ v \cdot n + v \wedge n ] n^{-1}

The first term is the component of v along n.  So, the reflected v is just

v' =  -v \cdot n n^{-1} + v \wedge n  n^{-1}

A small manipulation lets us write

v' =  -n \cdot v n^{-1} - n \wedge v  n^{-1}
  =  - [nv] n^{-1} = - nvn^{-1} 

Kinda cute. And, due to Hamilton, this gets us halfway to rotations, because he noticed that a rotation is simply two reflections. Say we reflect along b, followed by a:

v_{rotated} = (ab)v(ab)^{-1} = RvR^{-1}

R is known as a rotor: a product of two unit vectors.

R = ab = a \cdot b + a \wedge b

We can find the magnitude of a \wedge b by writing

ba =  b \cdot a + b \wedge a = a \cdot b - a \wedge b

and then considering the following product:

abba = a^2 b^2 = 1 = (a \cdot b)^2 - (a \wedge b)^2

Since a \cdot b is \cos \theta we can write

1 - \cos^2 \theta = \sin^2 \theta = - (a \wedge b)^2

So a \wedge b is a bivector whose magnitude is \sin \theta and square is negative. Let I be the unit bivector

I = \frac{a \wedge b}{\sin \theta}

and write

ab = R = \cos \theta + I \sin \theta = \exp (I \theta)

Looks like the common exponential phase factor e^{i \theta}. Aside: what are the complex numbers?  In two dimensions, vector (a,b) is related to complex a + ib like so: a \hat{x} + b \hat{y} = \hat{x} (a + \hat{x} \hat{y} b) = \hat{x} (a + I b). Just pre-multiply by \hat{x}, selecting the real axis. You always knew there was something like this going on behind the scenes.

Moving along: let's use the dagger operator to reverse the order of vector products: (ab)^\dagger = ba . Since unit vectors are their own inverse, we can write y as a rotated version of x like so:

y = R x R^{-1} = R x R^\dagger 

If R is in fact a function of time, we can consider \dot{y} :

\begin{align} \dot{y} &= \dot{R} x R^\dagger + R x \dot{R^\dagger} \\ &= \dot{R} R^\dagger y + y R  \dot{R^\dagger} \\ &= (\dot{R} R^\dagger) y - y (\dot{R}R^\dagger) \end{align}

For the last step, take the time derivative of R R^\dagger = 1 and show \dot{R} R^\dagger = - R \dot{R}^\dagger.

Let \Omega= - {1 \over 2} \dot{R} R^\dagger  . \Omega is apparently of even grade, and has no scalar part. \Omega must be a bivector, and we can write:

\dot{y} = - \Omega\cdot y = y \cdot \Omega

Orbital Dynamics

With rotational motion in our toolkit, let's develop the first few results in central-force dynamics. A nice trick for describing this is to shift the dynamics to a rotor. We accomplish this by considering a vector x as a rotation of some basis vector, plus a stretch.

x= U e_1 U^{\dagger}

We are now allowing a stretch as well as rotation, so U is a little more than a rotor: we are now considering a general even element. In three dimensions this is a scalar plus bivector [side note: the spinor and quaternion concepts fall out of this]. This presents us with a slight issue right away, in that U has four degrees of freedom, but we only need three for x. This allows us to apply a constraint on U. But before deciding on that constraint, consider the rate of change of x:

\dot{x} = \dot{U} e_1 U^\dagger + U e_1 \dot{U}^\dagger

Under the special case where \dot{U} e_1 U^\dagger = U e_1 \dot{U}^\dagger (this is our constraint) we can write

\dot{x} = 2 \dot{U} e_1 U^\dagger

Introduce a new variable s, such that {dt \over ds} =r= U U^\dagger

2 {dU \over ds} = \dot{x} U e_1
2 {d^2 U \over {ds}^2} = r \ddot{x} U e_1+ \dot{x} {dU \over ds} e_1 =  (\ddot{x} x+{1 \over 2} \dot{x}^2) U

The last step follows because r  U e_1 = x U. If we have inverse square central force motion

m \ddot{x} = -{k x\over r^3}

then we have

2 {d^2 U \over {ds}^2} =  (\ddot{x} x+{1 \over 2} \dot{x}^2) U
= ( -{k \over m} {x^2 \over r^3} + {1 \over 2} \dot{x}^2) U
=  {1 \over m} ( -{k \over r} + {1 \over 2}m \dot{x}^2) U
 {d^2 U \over {ds}^2} = \left( {E \over 2m}  \right) U

Harmonic motion. Nice.

Orbit Shape

A mass m, at r, moving with respect to some origin, defines a plane described by the bivector L, the angular momentum:

\begin{align*} L &\equiv r \wedge p \\ &= m r \wedge \dot{r}\\ &= m r \wedge (r \dot{\hat{r}} + \dot{r}\hat{r})\\ &= m r^2 (\hat{r} \wedge \dot{\hat{r}}) = m r^2 \hat{r} \dot{\hat{r}} \end{align*}

For motion in a potential V= -{k \over r} we have

\dot{v} = -{k \over m r^2} \hat{r}

Form the product of this with L:

L\dot{v} = -mr^2\dot{\hat{r}}\hat{r}  \left( {-k \over mr^2} \right) \hat{r} = k\dot{\hat{r}}

{d \over {dt}} (Lv - k \hat{r}) = 0

And we see that Lv- k \hat{r} is a constant of the motion. This vector, which sits in the plane of motion (L \wedge v = 0), is known as the Runge-Lenz vector. Let's be explicit about the conserved vector and call it e:
Lv = k \hat{r} + ke

With this definition, e is dimensionless. If we multiply through with r we have

\begin{equation} \label{eq2} Lvr = k \hat{r} r + ker  \end{equation}

The left hand side is

\begin{align} Lvr &= L (v \cdot r + v \wedge r)\\ &= L \left(v \cdot r + \frac{L^\dagger}{m} \right) \\ &= L (v \cdot r) + \frac{l^2}{m} \label{eq3} \end{align}

The right hand side is

\begin{align*} k \hat{r} r + ker &= k \abs{r} + k(e \cdot r + e \wedge r)   \\ &= k \abs{r} + \abs{e} \abs{r} \cos \theta + e \wedge r \end{align*}

So we have, finally

l^2/m + (r \cdot v) L = k \abs{r} + k \abs{e} \abs{r} \cos \theta + e \wedge r

The scalar part is

l^2/m = k \abs{r} + k \abs{e} \abs{r} \cos \theta

or

\abs{r} = \frac{l^2/mk}{1+\abs{e} \cos \theta}

and the bivector part is

(r \cdot v) L = e \wedge r  

or

L = \frac{e \wedge r }{r \cdot v}

Returning to \eqref{eq2} we can develop a relation between E, and l and e

\begin{align*} (Lv - k \hat{r})^2 &= k^2 e ^2 \\ (Lv)^2 - 2k(Lv) \cdot \hat{r} + k^2 &= k^2 e^2 \\ l^2 v^2 -2k \frac{\left< Lvr \right>}{r} &= k^2 (e^2 -1) \end{align*}

Using \eqref{eq3}

\begin{align*} l^2 v^2 - \frac{2kl^2}{mr} &= k^2 (e^2 -1)\\ \frac{2 l^2}{m} \left( \frac12  m v^2 - \frac kr \right) &= k^2 (e^2-1) \\ E &= \frac{m k^2}{2 l^2} (e^2 -1) \end{align*}